Pengaruh Pendidikan Terhadap Mobilitas Sosial di Masyarakat Perkotaan - Padang, Poliman; Tamba, Ida Nurjana; Manik, Vinolya Lidevia Br; Yunita, Sri (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of education on social mobility in urban communities. This research uses a qualitative approach through the literature study method. The data collection technique used is all materials that are in line with this writing problem, by examining the results of the research, citing books, studying theories related to the problem. The main source of research data is research articles published in various scientific journals and indexed on the google scholar database. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawn. The results of the analysis show that education has a significant impact on social mobility in urban communities, such as increasing social status, improving the economy, increasing opportunities, and increasing awareness. In the life of urban people, the increasing needs of life trigger the lifestyle tendency of materialism, consumerism, and hedonism, as well as the increase in violence, drug use, and the rapidly growing flow of information